Pengaruh Disiplin Kerja dan Keselamatan Kerja terhadap Kinerja Karyawan pada PT Pratama Abadi Industri Divisi Stockfit Tangerang Selatan - Fathan Arif; Umar Hanis (ProBank, 2026)
This study aims to determine the effect of work discipline and work safety on employee performance at PT Pratama Abadi Industri, Stockfit Division, South Tangerang. This research uses a quantitative approach with data collected through questionnaires. The sample consisted of 84 respondents selected using the Slovin formula. Data analysis techniques included validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that work safety has a positive and significant effect on employee performance, as indicated by the t-test result where tcount is greater than ttable. Work discipline also has a positive and significant effect on employee performance. Simultaneously, work discipline and work safety significantly affect employee performance. These findings indicate that improving employee discipline and strengthening workplace safety practices are important factors in supporting better employee performance. The results of this study are expected to provide practical input for company management in improving employee productivity through better safety systems, discipline implementation, supervision, and employee appreciation.